2015
DOI: 10.1002/aur.1494
|View full text |Cite
|
Sign up to set email alerts
|

Local brain connectivity across development in autism spectrum disorder: A cross‐sectional investigation

Abstract: Lay Abstract There is a general consensus that autism spectrum disorder (ASD) is accompanied by alterations in brain connectivity. Much of the neuroimaging work has focused on assessing long-range connectivity disruptions in ASD. However, evidence from both animal models and postmortem examination of the human brain suggests that local connections may also be disrupted in individuals with ASD. Here we investigated the development of local connectivity across three age cohorts of individuals with ASD and typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
100
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 58 publications
14
100
3
Order By: Relevance
“…The finding that the complex functional cortical architecture can be broken down into a small number of connectivity motifs may lead to breakthroughs in our understanding of cortical computation at the circuit level. Given that numerous neuropsychiatric and neurological diseases–such as autism spectrum disorders and epilepsy–may be associated with cell type-specific connectivity change in cortical microcircuits (18, 38, 39), such a detailed blueprint of cortical microcircuits could serve as an invaluable platform for screening and pinpointing specific circuit abnormalities in animal models of disease, thus providing a path to the development of comprehensive circuit-based, cell type-specific interventions that are otherwise not addressable with current treatments.…”
Section: Resultsmentioning
confidence: 99%
“…The finding that the complex functional cortical architecture can be broken down into a small number of connectivity motifs may lead to breakthroughs in our understanding of cortical computation at the circuit level. Given that numerous neuropsychiatric and neurological diseases–such as autism spectrum disorders and epilepsy–may be associated with cell type-specific connectivity change in cortical microcircuits (18, 38, 39), such a detailed blueprint of cortical microcircuits could serve as an invaluable platform for screening and pinpointing specific circuit abnormalities in animal models of disease, thus providing a path to the development of comprehensive circuit-based, cell type-specific interventions that are otherwise not addressable with current treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Functional connectivity, at least, seems to trend from hyperactivity in childhood towards normalization or hypoactivity in older age (Dajani & Uddin, 2016;Nomi & Uddin, 2015). Anatomically, the increased grey matter seen in primary motor cortex by Mahajan et al in autistic children is contradicted by a relationship between reduced grey matter and poorer finger-tapping in autistic adults (Duffield et al, 2013).…”
Section: The Neuroanatomical Correlates Of Movement Impairmentmentioning
confidence: 97%
“…Short-range FC, quantified as regional homogeneity (ReHo) (Zang et al, 2004), has also been defined as the connectivity of a given voxel to those of its nearest neighboring voxels, ranging from 6 voxels (Shukla et al, 2010) to 26 voxels (e.g. Anderson et al, 2014; Dajani and Uddin, 2016; Lopez-Larson et al, 2011). In addition, short-range FC has been defined as the connectivity within the same lobe (e.g.…”
Section: What Is Short-range Structural and Functional Connectivity?mentioning
confidence: 99%
“…In studies that incorporated ReHo analyses of fMRI data, there was an increase in short-range connectivity in default-mode network (DMN), visual, motor resting-state networks in individuals with ASD (6–17 years) (Washington et al, 2014) while other studies found more mixed results such as both hypo- and hyperconnectivity of short-range connections (e.g. Dajani and Uddin, 2016; Maximo et al 2013; Shukla et al, 2010). Specifically, individuals with ASD showed decreased short-range FC in superior parietal and prefrontal regions (Shukla et al, 2010), middle/posterior cingulate and medial frontal regions (Maximo et al, 2013), sensory processing brain regions (Dajani and Uddin, 2016) and increased short-range FC in lateral and medial temporal regions (Shukla et al, 2010), occipital and posterior temporal regions (Maximo et al, 2013) and complex information processing regions (Dajani and Uddin, 2016).…”
Section: Atypical Development Of Short-range Connectivity In Humanmentioning
confidence: 99%
See 1 more Smart Citation